2003
DOI: 10.1034/j.1399-0004.2003.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

The allelic loss of chromosome 3p25 with cmyc gain is related to the development of clear‐cell renal cell carcinoma

Abstract: To explore the role of allelic losses at 3p25 and genetic alterations of chromosome 8, we investigated the relationships between genetic alterations in these chromosomal regions and clinicopathologic findings (such as tumor size and grade), by employing fluorescence in situ hybridization (FISH). Fifty Japanese clear-cell renal cell carcinomas (RCCs) were examined by dual-color FISH using cosmid DNA probes for 3p25.1-25.3 combined with probes for chromosome 3 centromere, 8p12, 8p21.1, 8p21.3, 8p22 and 8q24.12-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Finally, our FISH results showed loss of chromosome 3 or 3p in epithelial cells of all 3 tumors. Previous FISH analyses indicate that sporadic CCRCC harbors monosomy for chromosome 3 and deletion of 3p in 26% to 36% and 45% to 76% of cases, respectively [6][7][8], whereas the loss of large regions of genetic material from chromosome 3 is rare in other types of RCC [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 97%
“…Finally, our FISH results showed loss of chromosome 3 or 3p in epithelial cells of all 3 tumors. Previous FISH analyses indicate that sporadic CCRCC harbors monosomy for chromosome 3 and deletion of 3p in 26% to 36% and 45% to 76% of cases, respectively [6][7][8], whereas the loss of large regions of genetic material from chromosome 3 is rare in other types of RCC [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 97%
“…33 Accordingly, previous reports have illustrated that in some cases, FISH using bacterial artificial chromosome or cosmid probes can detect deletions in 3p to genetically establish a diagnosis of clear cell RCC. 34,35 In our series, karyotyping and/or FISH was successful in 44 of the 74 cases where a portion of the FNA was submitted for cytogenetic analysis. Specific, abnormal cytogenetic profiles were seen in 27 of these cases and the results were concordant with the cytomorphologic impression of the renal tumor except in 1 unusual case.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are involved in cell cycle progression, apoptotic cell death, glycolysis, glutaminolysis, and lipid synthesis. By employing fluorescence in situ hybridization, the deletion at 3p25.1–25.3 with c-myc gain had a significant correlation with tumor size in ccRCC [56]. Furthermore, an in vitro study indicated that c-myc knockdown significantly inhibited ccRCC cell proliferation by arresting the cell cycle in the G0/G1 phase [57].…”
Section: Discussionmentioning
confidence: 99%